The Importance of the Governance Network in the Innovation Policy Processes - Kopyciński, Piotr (Journal of Public Governance, 2009)
The article presents problems of governance network in the context of regional innovation processes. The author presents selected definitions of network and focuses on the nature of the governance network. He concentrates on two main research directions: Social Network Analysis and Policy Network Studies; he reviews the basic concepts associated with innovation processes, which gives an outline of governance network processes within a regional innovation system. To that end, the author uses the results of research carried out by the Malopolska School of Public Administration in the Cracow University of Economics. Based on these results, he describes selected processes of the governance network operation in the Malopolska Voivodship. The closing part of the article contains a summary and conclusions concerning the governance network processes.